La sobre explotación laboral y discriminación a los Docentes Ecuatorianos con las ocho horas reloj del art 117 de la LOEI, que vulnera el derecho garantizado en la constitución a igual trabajo, igual remuneración - Paredes Benavides, Pilar del Carmen (2016)
Education is a necessity for society, teachers anywhere in the world should be treated with dignity, and as a special worker, because we must remember that if there were no teachers, there would be no diversity of professionals who are in the Currently, up to the year 2010 were working six hours teaching, and the remaining teachers covered them in their homes, to conduct examinations, qualifications, training materials, etc., but from that date to reform the ladder changing the name Act now LOEI, has been attacking the rights of teachers, because even before that worked six hours teaching were recognized economically, as it should be, especially now already famous wage equalization was done, teachers are still discriminated against and exploited occupationally, subject to a schedule that does not reflect at any time the treatment or occupational health that teachers must have in their institutions, since they are not in most of Ecuador adequate infrastructure and properly in both technically and worse health for teachers staying more than eight hours in the same clock, being Civil Servants is everyone who receives a payment from the state, but when you have the right conditions and fair pay, equal pay for equal work also currently not in ISSE, teachers can take care of their disease because it has become an eternal pilgrimage catching a turn to any doctor, leading teachers to go to the classroom ill, thinking about other things, but in their work because teachers are a big part of over-indebted, that exist in the country impoverished by the salary they receive. So to really improve education, the Ministry of Education and the government itself must understand that teachers are not to blame for the crisis itself, but the incorrect application of the curricular reforms that have rhyme or justifying thus the eight clock hours they are now required teachers, will not improve the quality of education, but to make it worse, because the health of teachers is going to be most affected, since they have to be out consultations either Insurance or other physicians to seek solutions to their health, it can not properly play in the classroom, which obviously will lead to education in the classroom is not good, not because he so wanted, but because there is the right environment for their health and life, in addition to psychological and clinical studies, the brain of a person and by age can withstand a time limit noise, talking, screaming, then you obviously need a rest and tranquility, which at night is not fully accomplished, because never the brain rests completely, is always working, but apparently we are asleep, and a teacher who will leave at 5 am from home without breakfast and return to the six, seven of night, completing tasks at home, much less will properly rest